Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja melalui Motivasi Kerja sebagai Variabel Mediasi pada PT INKA Multi Solusi - Jihan Salsabila; Nurul Indawati (J-MAS (Jurnal Manajemen dan Sains), 2026)
This study aims to examine the effect of workload and work environment on job satisfaction with work motivation as a mediating variable at PT INKA Multi Solusi. The study employed a quantitative approach with a causal research design. Data were collected through questionnaires distributed to 112 employees selected using purposive sampling based on the Slovin formula. The data were analyzed using Partial Least Squares (PLS) with SmartPLS 4.1.1.6 software. The results indicate that workload and work environment have a positive and significant effect on work motivation. In addition, workload, work environment, and work motivation positively and significantly affect job satisfaction. The findings also show that work motivation mediates the relationship between workload and job satisfaction, as well as the relationship between work environment and job satisfaction. This study is limited to employees of PT INKA Multi Solusi. Therefore, future research is recommended to involve broader organizational contexts and additional variables. Practically, the findings provide implications for companies in improving job satisfaction through effective workload management, supportive work environments, and enhanced employee motivation.